Java SOA cookbook - Hewitt, Eben (O'Reilly Media, Inc., 2009)
Chapter 2. XML Schema and the SOA Data Model; 2.0 Introduction; 2.1 Designing Schema for SOA; Problem; Solution; Russian Doll; Salami Slice; Venetian Blind; See Also; Garden of Eden; 2.2 Creating Canonical Data Model; Problem; Solution; Discussion; Defining the canonical data model; Recommendations; Updating the canonical data model; See Also; 2.3 Using Chameleon Namespace Design; Problem; Solution; 2.4 Versioning Schemas; Problem; Solution; Discussion; Use the version attribute; Hack the root element; Change the name or URI of the schema document.